Comprehensive pan-cancer analysis identifies PLAG1 as a key regulator of tumor immune microenvironment and prognostic biomarker - Ruicheng Wu; Ruicheng Wu; Dengxiong Li; Shuxia Zhang; Jie Wang; Qingxin Yu; Dechao Feng; Dechao Feng; Ping Han (Frontiers in Immunology)
BackgroundThe literature on the role of pleomorphic adenoma gene 1 (PLAG1) in malignant tumors is limited. This study aimed to perform pan-cancer analysis of PLAG1.MethodsThe expression of PLAG1 was analyzed by Human Protein Atlas (HPA). The differential expression and prognosis of PLAG1 were analyzed based on TCGA pan-cancer data. The relationship between PLAG1 expression and tumor heterogeneity, stemness and immune infiltration was investigated. The enrichment analysis and biological function of PLAG1 in bladder cancer were analyzed.ResultsThe expression of PLAG1 was increased in a variety of tumors and significantly correlated with the prognosis of patients. Their expression levels were associated with key immune checkpoint genes (CD274, HAVCR2), immune infiltration and immune stimulation factors (CD48, CD27). In bladder cancer, functional enrichment analysis indicated that PLAG1 was involved in epidermal related processes and immune pathways. PLAG1 gene expression reduction can significantly inhibit the proliferation of bladder cancer cells.ConclusionsPLAG1 has the potential to be a prognostic marker and a potential therapeutic target for patients with malignant tumors.